Retrieval of broken file and retreatment of previously treated mandibular left second molar - Paramastri, Sukma; Fitriningtyas, Kurnia; Santosa, Pribadi; Mulyawati, Ema; Rinastiti, Margareta; Kristanti, Yulita (Majalah Kedokteran Gigi Indonesia, 2023)
Broken files in the root canal system which are not removed may interfere with thorough cleaning of the root canals. As a result, they cannot be hermetically obturated. This imperfect cleaning can leave necrotic tissue which can potentially cause failure in root canal treatment. The purpose of this paper is to describe the management of retrieval of broken files and re-treating root canals in previously treated mandibular left second molars. The retrieval of the broken file used conventional techniques combined with a Satelec ultrasonic scaler to remove the files from the root canal. It was operated under an endodontic microscope, and after retreatment of the root canal, the tooth was restored with final restoration of endocrown. Retrieval of fractured files using conventional techniques combined with Satelec ultrasonic scaler and the root canal re-treatment followed by final endocrown restoration could restore all four tooth functions properly.